IMPLEMENTING JOB DESCRIPTIONS IN MOSQUE ORGANIZATIONAL STRUCTURES TO SUPPORT ACTIVITY PROGRAMS - Sugiharto; Rafiah Afsah Ramadhani Ramadhani; Faris Faqih; Gendis Ayu Lestari; Ridho Al Rasyid (Program Studi Manajemen Dakwah - Fakultas Dakwah dan Ilmu Komunikasi - UIN Syarif Hidayatullah Jakarta, 2026)
Mosques play an important role as centers of worship, da'wah, education, and social activity. The diverse implementation of mosque programs requires effective organizational management through a clear division of tasks. This study aims to analyze the implementation of job descriptions within mosque organizational structures and their influence on mosque activity programs. The research employs a library research method by reviewing literature related to mosque management, organizational structure, and job descriptions. The findings indicate that clear job descriptions improve program effectiveness through well-defined task allocation, better inter-departmental coordination, and increased accountability among mosque administrators. Therefore, job descriptions are an important factor in achieving professional and congregation-oriented mosque management. Keywords: Job Descriptions, Organizational Structure, Mosque Management, Mosque Administrator.